The Macapagal-Arroyo presidency and administration (2001-2010) - Abueva, Jose V. (Quezon City : Center for Leadership, Citizenship and Democracy, National College of Public Administration and Governance, University of the Philippines, 2014)
Fourth UP public lectures on Philippine presidency and administration
Keywords: Arroyo administration -- 2001-2010.; Arroyo, Gloria Macapagal; Philippines -- Politics and government